Islamisasi Di Asia Tenggara: Proses Kedatangan, Kepribadian Dan Karakteristik Islam Di Asia tenggara - Oktia, Reni; Seprina, Reka (Universitas Negeri Padang, 2024)
This research aims to find out about the process of the arrival of Islam, the personality and characteristics of Islam in Southeast Asia. This research is qualitative research using the library study method (literature study), by collecting sources that contain research coverage that has been previously examined and is relevant, consisting of textbooks, periodicals, scientific journals, articles and other relevant research. The research results explain the first few points. The process of Islam's arrival in Southeast Asia is a complex and varied phenomenon, involving various channels such as trade, missionary preaching and political interaction. This process has shaped an Islamic identity in Southeast Asia, which includes a fusion of Islamic teachings with local culture and traditions, as well as a dynamic response to historical and social change. Second, there are four main theories about the origins of Islam in Southeast Asia that are debated in discussing the arrival, spread and Islamization of Southeast Asia, namely Indian Theory, Arab Theory, Chinese Theory and Persian Theory. Third, the character of Islam in Southeast Asia is reflected in the diversity of culture, beliefs and religious practices that are characteristic of Southeast Asia.